Land Use Governance and Smart City Policy Frameworks for Sustainable Urban Development in the Philippines - Carlo Antonio Dela Cruz; Francesca Isabel Bautista; Daniel Joseph Villanueva (Adaptive Governance Research, 2026)
Purpose: This study examines the influence of land use governance and smart city policy frameworks on sustainable urban development in the Philippines and evaluates their relative contributions to promoting resilient and inclusive urban growth. Subjects and Methods: A quantitative cross-sectional survey design was employed involving 241 stakeholders engaged in urban planning and governance, including local government officials, urban planners, environmental officers, academics, and community representatives. Data were collected using a structured questionnaire based on a five-point Likert scale and analyzed through descriptive statistics, validity and reliability testing, Pearson correlation analysis, and multiple regression analysis. Results: The findings indicate that both land use governance and smart city policy frameworks significantly and positively influence sustainable urban development. The regression model explained 65.0% of the variance in sustainable urban development (R² = 0.650), with land use governance demonstrating a stronger effect (β = 0.486, p < 0.001) than smart city policy frameworks (β = 0.382, p < 0.001). These results suggest that effective governance, characterized by institutional coordination, regulatory implementation, and stakeholder participation, provides the institutional foundation for sustainable urban development, while smart city policies enhance governance through digital innovation and data-driven decision-making. Conclusions: Sustainable urban development in the Philippines is best achieved by integrating adaptive land use governance with smart city policy implementation. Strengthening Comprehensive Land Use Plans (CLUPs), enhancing Local Government Unit capacity, expanding Geographic Information Systems (GIS), promoting open spatial data, and adopting smart zoning strategies can support more resilient, efficient, and sustainable urban governance.